kumarneupane4344 wrote:
saumik wrote:
Choose the point (a, b) = (1, -1)
A. (-b , -a) = (1, -1)
B. (–a, –b) = (-1, 1)
C. (b, –a) = (-1, -1)
D. (a, –b) = (1, 1)
E. (–b, a) = (1, 1)
Only choice A is equivalent to our assumed point, i.e, both their x and y coordinates have the same signs.
The answer is A.
Sir, will option A true for all co ordinates?
Yes, as long as you take co-ordinates from 2nd and 4th quadrants.
We assumed the point(1, -1), which is in the 4th quadrant. We proved this as true.
Let's choose (a, b) = (4, -5), which is at 2nd quadrant. Now, (-b , -a) = (5, -4). That's in the 2nd quadrant too. So this is true.
Note that points from 1st and 3rd quadrants won't hold true. We only need to prove one case as true to choose option A.